2020
DOI: 10.1080/20008198.2019.1694348
|View full text |Cite
|
Sign up to set email alerts
|

When does grief become pathological? Evaluation of the ICD-11 diagnostic proposal for prolonged grief in a treatment-seeking sample

Abstract: Rosner (2020) When does grief become pathological? Evaluation of the ICD-11 diagnostic proposal for prolonged grief in a treatment-seeking sample,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
(55 reference statements)
4
10
0
2
Order By: Relevance
“…They conclude that the existing criteria sets do not identify the same diagnostic symptom cluster. Similar findings were found in a German treatment-seeking sample ( 5 ), showing larger prevalence rates for PGD (69%) compared to PCBD (48%). Studies have shown that pathological grief differs from other disorders such as depression and PTSD and described a distinct diagnosis ( 4 ).…”
Section: Introductionsupporting
confidence: 85%
“…They conclude that the existing criteria sets do not identify the same diagnostic symptom cluster. Similar findings were found in a German treatment-seeking sample ( 5 ), showing larger prevalence rates for PGD (69%) compared to PCBD (48%). Studies have shown that pathological grief differs from other disorders such as depression and PTSD and described a distinct diagnosis ( 4 ).…”
Section: Introductionsupporting
confidence: 85%
“…(7)]. Similarly, in treatment-seekers, minimal PGD ICD-11 criteria correctly classified people against a relatively lenient standard of 30 or higher on the ICG (6, 7), yet as many as six additional symptoms were necessary to yield comparable prevalence and good diagnostic agreement with PGD 2009 and PCBD (5). Moreover, one study demonstrated the influence of the number of additional symptoms on symptom heterogeneity, theoretically demonstrating that the number of ways to meet PGD ICD-11 criteria ranges from 3.069 for one to 528 for seven additional symptoms (2).…”
Section: Multiverse Analyses In Research On Pgd Icd-11mentioning
confidence: 95%
“…Recent years have seen a surge of research and clinical awareness of stress-related disorders like PTSD [39] or prolonged grief [40, 41]. Just as important, if not even more frequent and more important, are social and interactional stressors.…”
Section: Causes Of Embittermentmentioning
confidence: 99%